The Ontological Reconstruction of the Problem of the Virtue-Happiness Concord: On the Tripartite Identity of Dé-Fú-Jié - Lin, Feng (Cosmos and History: The Journal of Natural and Social Philosophy, 2025)
Abstract: This paper aims to provide a novel ontological solution to the ancient problem of the virtue-happiness concord. Traditional solutions have reached an impasse because they have consistently sought answers within an ethical or theological framework. This paper argues that the root of the problem is not ethical, but ontological. To this end, it proposes and defends the theory of the tripartite identity of Dé-Fú-Jié. This theory reveals that our gifted potentiality (Dé), phenomenal fulfillment and happiness (Fú), and the possibility of annihilation as the immanent limit of being (Jié) are not three conflicting, independent elements, but are identical at the ontological root. The core thesis of this paper is that it is precisely this deep ontological unity that necessarily causes the disunity of virtue and happiness that we experience in the phenomenal world. This conclusion not only reinterprets the problem of evil and suffering but also lays the foundation for a new ethics based on an "asymmetrical responsibility" to "Life" itself.